Ichthyofauna diversity on artificial reefs in kilo lima coastal waters, Banggai Regency, Central Sulawesi - Samsu Adi Rahman; Indradi Noor Akbar; M. Arief Dharmawan; Nia Fahira; Achmad Alvinsyah Rasyidi; Sifa Amalia; Rizky Aulia Sari (Acta Aquatica: Aquatic Sciences Journal, 2026)
Degradation of natural coral reef ecosystems in the coastal waters of Kilo Lima Beach due to anthropogenic activities has led to a decline in reef fish populations. The installation of artificial reefs has emerged as a rehabilitation strategy to provide new habitats for marine biota. This study aims to identify species diversity, population abundance, and the distribution of ichthyofauna across three types of artificial reef structures (Kubah, Dinoreef, and Carreef) in the waters of Kilo Lima Beach, Banggai Regency. This study evaluates the effectiveness of artificial reefs in Kilo Lima waters (April 2025–April 2026) using the Underwater Visual Census (UVC) method. Results indicate that artificial reefs significantly increase reef fish richness and density. Dinoreef recorded the highest species richness (47 species), while carreef reached the highest population density (5.7 ind/m²). The community is dominated by major fish groups (>80%), confirming the artificial reefs' function as a refuge area. The highest diversity index was achieved five months post-deployment (H’ = 3.50) before declining due to the dominance of specific species. The presence of associated biota and optimal water quality confirm a successful ecological succession. In conclusion, artificial reefs are effective in rehabilitating marine ecosystems, though long-term monitoring is essential for optimal community stability. Keywords: Artificial Reefs; Banggai; Diversity; Ichthyofauna; Kilo Lima